Peran Manajemen Sumber Daya Manusia Stratejik Terhadap Kinerja Perusahaan (Studi Kasus Pada Perusahaan Jasa PT. PJBS di Sidoarjo) - Berlia Setiawan; Lena Ellitan (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2025)
The basic concept of strategic human resource management (SHRM) is presence of a system within an enterprise that is planned and designed to achieve a sustainable comparative advantage through its human resources. In measuring or analyzing SHRM at a company that uses aspects include strategic human resource conditions, the internal changes that occur in strategic human resources, the condition of the gaps, obstacles encountered in the development of human resources and its strategic actions to overcome these barriers, attitudes the development of strategic human resource management, corporate response to human resource development and the strategic approach taken by managers to strategic HR in a company. This research is a descriptive study, the research aims to describe the phenomenon and context in implementation of SHRM in PT.PJBS. The approach used is an exploratory qualitative approach, the research aims to obtain preliminary information on SHRM applied to PT. PJBS and its relationship to company performance. The results showed that the condition of strategic human resource management which is owned by PT. PJBS is good enough and strong enough to be able to compete with other similar companies. The role of strategic HRM to the achievement of the company's performance is considered very positive. As the core assets of PT PJBS, human resources participating in the achievement of the company's performance with a range of competency. Corporate performance is measured through key performance index (KPI), two of which are domains of HR, which is HCR and OCR. Based on the results of this study submitted suggestions to the PT. PJBS is to recast the job description for each position, and to develop a portfolio of projects and improve TNA.